2010
DOI: 10.2981/09-034
|View full text |Cite
|
Sign up to set email alerts
|

Home‐range size and spatial organization of black‐footed ferrets Mustela nigripes in South Dakota, USA

Abstract: Effective conservation planning for endangered species depends on an understanding of space use patterns. Blackfooted ferrets Mustela nigripes depend on prairie dogs Cynomys sp. as prey and use their burrow systems for shelter. The availability of areas with high densities of active prairie dog burrows is the major factor thought to affect their selection of sites and resources. However, we have little knowledge about how the spatial distribution of active prairie dog burrows might influence the spatial organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 57 publications
3
37
0
Order By: Relevance
“…2), but not males. In addition, the negative correlation between sizes of UD ranges and densities of active burrow openings was significant for female ferrets in the study of Jachowski et al (2010). Therefore, these two studies collectively suggest that female ferrets tend to use smaller areas where active burrow openings are abundant, a trend that agrees with studies of other Mustela and the hypothesis that female Mustela are most concerned with acquisition of resources to support young, whereas males are more concerned with breeding (Erlinge and Sandell 1986, Sandell 1986, 1989.…”
Section: Space Use and Resource Selectionsupporting
confidence: 79%
See 2 more Smart Citations
“…2), but not males. In addition, the negative correlation between sizes of UD ranges and densities of active burrow openings was significant for female ferrets in the study of Jachowski et al (2010). Therefore, these two studies collectively suggest that female ferrets tend to use smaller areas where active burrow openings are abundant, a trend that agrees with studies of other Mustela and the hypothesis that female Mustela are most concerned with acquisition of resources to support young, whereas males are more concerned with breeding (Erlinge and Sandell 1986, Sandell 1986, 1989.…”
Section: Space Use and Resource Selectionsupporting
confidence: 79%
“…Many studies suggest ferrets exhibit a developmentally fixed predisposition to defend space, perhaps regardless of habitat quality, which would limit the number of ferrets a habitat supports, thus supporting model 2 (Biggins et al 1985, Paunovich and Forrest 1987, Richardson et al 1987, Fagerstone and Biggins 2011, Livieri and Anderson 2012. However, in a recent study, Jachowski et al (2010) reported a few instances of intense same-sex space use overlap during June-October when adult female ferrets were rearing their young (i.e. kits).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…We present an examination of space use, resource selection, and territoriality by adult ferrets during the post-breeding season on a colony of blacktailed prairie dogs (hereafter prairie dogs, C. ludovicianus) in the Conata Basin, South Dakota, USA. The study colony was immediately adjacent to, and contained somewhat higher densities of burrow openings (144.7 ha 1 ) than the colony surveyed by Jachowski et al (2010: 129.3 ha 1 ). Overall, we hoped to increase understanding of the spatial ecology of M. nigripes and to evaluate the competing models for reserve design.…”
mentioning
confidence: 99%
“…Prairie dog colonies differ in size, and contain varying densities of prairie dogs. In colonies with high densities of prairie dogs, ferrets can shrink their territories (Jachowski et al 2010) but it is unclear if ferrets tend to inhabit overlapping territories (model 1) or become crowded and compete for space (model 2). Many studies suggest ferrets exhibit a developmentally fixed predisposition to defend space, perhaps regardless of habitat quality, which would limit the number of ferrets a habitat supports, thus supporting model 2 (Biggins et al 1985, Paunovich and Forrest 1987, Richardson et al 1987, Fagerstone and Biggins 2011, Livieri and Anderson 2012.…”
mentioning
confidence: 99%